Culturological potential of performative practices in the system of training a modern choreographer - Yefimova, Olena; Kosychenko, Viktoriia (Professional Art Education, 2025)
Object. The article is devoted to the analysis of the integration of performative practices into the system of professional training of choreographers in the context of the transformation of Ukrainian art education and its adaptation to international standards. The essence of performative art, its historical origins, and key characteristics that distinguish it from traditional choreography are clarified. Methods & methodology. The methodological framework is based on the analysis of scholarly sources in the theory of choreography and performative art, comparative analysis of educational practices, structural-functional analysis of methodological approaches, as well as content analysis of curricula. An interdisciplinary approach (choreography – theatre practices – cultural studies) is applied, along with the principles of practice-oriented learning and creative interdisciplinary interaction. Scientific novelty. For the first time, methodological tools for integrating performative practices into choreographers’ training have been systematized, and their potential for shaping complex artistic thinking has been identified. The complementarity of performative art and traditional choreography is substantiated, and key challenges that hinder their implementation in the educational process are highlighted. Results. Effective forms and methods of teaching are outlined: performance-based classes, workshops, creative laboratories, individual and group experimental tasks. Typical obstacles to integration are identified – insufficient teacher training, lack of clear assessment criteria, inertia of educational program content, and low student motivation for experimental activity. It is demonstrated that the application of performative approaches activates students’ creative potential, develops analytical thinking, and fosters the ability to work in an interdisciplinary environment. Conclusions. It is concluded that the integration of performative practices into the professional training of choreographers enhances the innovative potential of art education and contributes to the modernization of the educational environment. The results of the study have both theoretical and practical significance and can be used to update the content of educational programs, develop new methodological modules, and implement innovative forms of professional training for future choreographers.